OPTIMIZATION SURGICAL TACTICS FOR THE TREATMENT OF CLOSED ABDOMINAL INJURIES AND THE POSSIBILITY OF MINIMALLY INVASIVE INTERVENTIONS - Norov Mirvohid Charievich; Mustafakulov Ishnazar Boynazarovich; Boynazarov Mehrojmirzo Eshnazarovich; Juraeva Zilola Aramovna (Research Focus International Scientific Journal, 2023)
Closed abdominal injuries with injuries to the hollow organs of the abdominal cavity are accompanied by high mortality, which, depending on the nature of the injuries, ranges from 27% to 35%. In this regard, the authors reviewed the literature on surgical treatment tactics for these injuries. The authors found that to date, the feasibility of various tactical concepts for correcting injuries in patients with combined abdominal injuries, the order of traditional and minimally invasive surgical interventions have not been determined, and a diagnostic and treatment algorithm for injuries to the hollow organs of the abdominal cavity during abdominal pain has not been developed. All these data serve as an objective basis for the need for further scientific research in this direction.